Regional Spanish Tourism Competitiveness. A DEA-MONITUR approach - Martín, Juan Carlos; Mendoza, Cira; Román, Concepción (REGION, 2017)
The aim of this paper is to analyse the regional tourist competitiveness performance in Spain. We use the seven pillars of tourism from a very detailed and complete database compiled by the Spanish Government –MoniTUR 2010 as primary data. Thus, we calculate a DEA-MONITUR regional tourist competitiveness index in order to compare and rank the total 17 Spanish Autonomous Communities using data envelopment analysis (DEA). Our results show how this performance is very different among regions, and the position of each of the laggard Autonomous Communities should be analysed by their respective destination management organizations (DMOs) in order to envisage adequate corrective measures.